Transition Metal Phosphide‐Based Materials for Efficient Electrochemical Hydrogen Evolution: A Critical Review - Weng, Chen‐Chen; Ren, Jin‐Tao; Yuan, Zhong‐Yong (ChemSusChem, 2020)
As hydrogen has been increasingly considered as promising sustainable energy supply, electrochemical overall water splitting driven by highly efficient non‐noble metal electrocatalysts has aroused extensive attention. Transition metal phosphides (TMPs) have demonstrated remarkable electrocatalytic performance, including high activity and robust durability towards hydrogen evolution reaction (HER) in acidic and alkaline as well as neutral electrolytes. In this Review, up‐to‐date progress of TMP‐based HER electrocatalysts is summarized. Various synthesis strategies of TMPs based on selected phosphorus sources are presented, and the reaction mechanisms of HER as well as the contribution of phosphorus in the TMPs to HER activity are briefly discussed. The multiscale approaches for promoting the activity and stability of TMP‐based catalysts are discussed with respect to intrinsic electronic structure, hybrids, microstructure, and working electrode interface. Some crucial issues and future perspectives of TMPs are pointed out. These modulated approaches and challenges are also instructive for constructing other high‐activity energy‐related electrocatalysts. Transitioning to hydrogen: In this Review, up‐to‐date progress of transition metal phosphide (TMP)‐based hydrogen evolution reaction (HER) electrocatalysts is summarized. Various synthesis strategies and the HER reaction mechanisms of TMP‐based catalysts are briefly discussed. In addition, multiscale approaches with respect to electronic structure, hybrids, microstructure, and working electrode interface are discussed for promoting HER performances.